2012
DOI: 10.1097/bot.0b013e3182724298
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Facilitate Fracture Repair in an Alcohol-Induced Impaired Healing Model

Abstract: Objectives Clinical studies have shown alcohol to be a risk factor for traumatic orthopaedic injuries and for nonunion. Data from animal studies suggest that alcohol exposure inhibits fracture healing. This report presents a novel rodent model of impaired fracture healing caused by repeated alcohol exposure. Using this model, we examined the regenerative effects of an intravenously administered population of isolated and expanded MSCs on fracture healing. Methods Bone marrow-derived MSC were isolated from tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
(50 reference statements)
0
35
0
3
Order By: Relevance
“…Many studies have outlined the ability of MSC to migrate and attach to a fracture environment, thereby contributing to callus formation and healing (30,31). There is much clinical interest in using MSC as an exogenous source to enhance fracture healing, and this has been already shown to partially reverse EtOH-induced deficits in fracture healing in animal models (9). It has been shown that TGF-␤1 contributes to induction of MSC differentiation into several cell lineages (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have outlined the ability of MSC to migrate and attach to a fracture environment, thereby contributing to callus formation and healing (30,31). There is much clinical interest in using MSC as an exogenous source to enhance fracture healing, and this has been already shown to partially reverse EtOH-induced deficits in fracture healing in animal models (9). It has been shown that TGF-␤1 contributes to induction of MSC differentiation into several cell lineages (25).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of MSC into osteoblasts and chondrocytes forms the fracture callus, which serves as the scaffolding for bone repair (7,8). Interestingly, exogenous intravenous administration of MSC to alcohol-exposed mice can partly reverse the deficits in fracture healing attributed to alcohol exposure (9). This raises the possibility of MSC use as a treatment modality.…”
mentioning
confidence: 99%
“…Depending on the fracture site, ~5-10% of fractures may result in delayed union or nonunion (2,3). Previously, autogenous bone grafts or free vascularized bone grafts have been widely used for nonunion treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cognitive, sensory, and motor deficits caused by the progression of AD, there are a number of behavioral and psychological symptoms related to dementia. These symptoms include agitation and aggression, wandering, disturbances in the sleep cycle, depression, anxiety, delusions and hallucinations (Ferri et al, 2004;de Vugt et al, 2005;Obermeyer et al, 2012). AD reduces the life expectancy of those affected, with an average survival time after diagnosis of 5-7 years (Fitzpatrick et al, 2005;Ganguli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Forgetfulness and difficulties with routine tasks are typically the initial symptoms. As the disease progresses, AD patients develop more severe memory loss, speech impairment, visual and spatial deficits, and loss of coordination and fine motor control (Rossor et al, 1996;Obermeyer et al, 2012;Alzheimer's Disease Internatinal, 2009). In addition to the cognitive, sensory, and motor deficits caused by the progression of AD, there are a number of behavioral and psychological symptoms related to dementia.…”
Section: Introductionmentioning
confidence: 99%